Efficient antibiotic removal from water using europium-doped poly(vinyl alcohol) nanofiber mats esterified with citric acid - Coin, Francesco (2024)
Increasing antibiotic pollution in water poses both environmental and health risks, contributing to an increase in antibiotic-resistant bacteria. This study proposes a novel adsorbent made of nanofibers of poly(vinyl alcohol) (PVA) created through electrospinning incorporating europium and citric acid that has exceptional adsorption capacities for ciprofloxacin (563.7 mg/g) and tetracycline (235.8 mg/g), two antibiotics of everyday use. Our findings demonstrate that this combination results in a swollen fiber structure where europium and citric acid remain immobilized even when in contact with water and promotes the creation of antibiotic chelation sites. Moreover, the adsorbent maintained its performance for four cycles and two reactivations. Finally, we studiedhow the adsorption of antibiotics is affected by other contaminants commonly found in water, such as dyes (methylene blue and/or rhodamine) and pesticides (atrazine). This innovative approach involving the use of esterified-doped PVA nanofiber has significant potential for enhancing remediation capacity and represents a promising solution for removing antibiotics from multipolluted water.